GAMBARAN HASIL PEMERIKSAAN MIKROBIOLOGI PADA AIR BERSIH BERDASARKAN DATA LABORATORIUM KESEHATAN DAERAH PADA BULAN OKTOBER HINGGA DESEMBER 2023 - Nofi Susanti; Putri Khairunnisa, Syalwa Uzla, Amanda Clarissa, Ayu Ananda, Widya Safira (CV. Adiba Aisha Amira, 2024)
Background: Clean water quality is determined by chemical, physical and bacteriological factors. Water for sanitation hygiene purposes has environmental health quality standards, one of which is biological parameters. Objective: The aim of this research is to identify water quality by testing microbiological parameters, namely coliform and e-coli bacteria. Method: This research uses cluster sampling and systematic sampling methods. Sampling is carried out only once for each sample tested. This research was conducted in October – December 2023 at the UPT Health Laboratory. The sample in this research was total sampling, namely the entire population was used as a research sample of 48 samples. Results: There were 48 results of microbiological examination of water, it was found that the highest frequency of total coliform examinations was according to the maximum standard (0/100ml) as many as 31 with a percentage of 64.6% and the frequency of E.coli examination was according to the maximum standard (0/100ml) as many as 30 with a percentage of 62.5%. Conclusion: Based on the results of clean water examinations carried out in the health laboratory with a total of 48 water samples, it shows that 30 samples with a percentage of 62.5% met the bacteriological requirements.